2002
DOI: 10.1063/1.1449892
|View full text |Cite
|
Sign up to set email alerts
|

Physical optics treatment of the shadowgraph

Abstract: We present an analysis of the shadowgraph method of visualizing convective flows based on physical optics, treating the refractive-index perturbation caused by the flow as a transmission grating. Various patterns in thermal convection of an isotropic fluid as well as normal rolls in electroconvection of a nematic liquid crystal are considered. The results differ significantly from those of geometrical optics, showing that use of the shadowgraph as a quantitative tool for amplitude measurements should not, in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
130
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(140 citation statements)
references
References 18 publications
8
130
0
Order By: Relevance
“…Different setups show different responses to the acquired signal as a function of the wave vector q, which is described by the so-called transfer function T (q) of the technique. It has been shown that the shadowgraph transfer function dependence upon the wave vector shows a sinusoidal behavior [48,53,54]:…”
Section: Dynamic Near-field Imagingmentioning
confidence: 99%
“…Different setups show different responses to the acquired signal as a function of the wave vector q, which is described by the so-called transfer function T (q) of the technique. It has been shown that the shadowgraph transfer function dependence upon the wave vector shows a sinusoidal behavior [48,53,54]:…”
Section: Dynamic Near-field Imagingmentioning
confidence: 99%
“…When the penetration depth is a macroscopic length ͑as it often is 9 ͒ shadowgraphy would be needed. 4,29 However, for a quantitative interpretation of experimental shadowgraphs, we shall need to also consider the effects of buoyancy and of the boundary conditions on the fluctuations. 4 Our theory can also provide a way to probe whether chemical equilibrium has been reached in the temperature gradient.…”
Section: A Light Scattering and Shadowgraphymentioning
confidence: 99%
“…͑39a͒ and ͑39b͒ that the decay rates of the fluctuations depend explicitly on the rate constant L r . Hence, measuring these fluctuations by light scattering 4,27 or shadowgraphy 4,29,30 in a reacting mixture provides information about the rate constant of the reaction. For instance, Letamendia et al 31,32 measured light scattering in various liquids with chemical equilibrium between two isomers.…”
Section: ͑33͒mentioning
confidence: 99%
“…All experiments were performed at a fixed inclination of γ = 30 • , within the regime of buoyancyinstability. Images of the convection pattern were collected using a digital CCD camera, via the usual shadowgraph technique [21,22]. Images were collected at 3 frames per second in one of two formats.…”
Section: Inclined Layer Convectionmentioning
confidence: 99%